Determining Type and Amount of Service Delivery Time by Teachers of Students with Visual Impairments: Results of a National Validation Study of the VISSIT. (March 2019) - Pogrund, Rona L.; Darst, Shannon; Munro, Michael
Introduction: This research followed the lead of an initial validation study and responded to the call from the state education agency–endorsed Service Intensity Subcommittee of the Texas Action Committee for the Education of Students with Visual Impairments to conduct a larger scale validation study on the Visual Impairment Scale of Service Intensity of Texas (VISSIT). Methods: The authors collected survey data from 77 respondents using a mixed-methods survey research design. These data were used to determine the VISSIT's validity and reliability. Participants represented urban, suburban, and rural geographic regions across 20 U.S. states. Results: The results of the national study showed that the VISSIT has social validity, which was supported by both ease of use and acceptability of the tool. The VISSIT's consequential and content validity were also supported by the data collected. The internal consistency reliability showed reliability for the VISSIT with a Cronbach's alpha calculated as being .935. Based on the results presented here, in which the social, consequential, and content validity of the VISSIT have been confirmed, it can also be confidently asserted that the VISSIT is construct valid. Discussion: The findings of this national study indicate an overall positive response to the usability and understandability of the VISSIT. Participants used the tool to provide quantifiable documentation to identify accurate student need for service across all expanded core curriculum areas as well as to provide administrators and families with research-based data to justify service type and time. Implications for practitioners: Respondents in the national study saw the VISSIT as an effective way to take student evaluation data and convert those results into a measurable recommendation for service type and intensity. The VISSIT helps a teacher of students with visual impairments to document how much time is needed for both direct and collaborative consultation services, as appropriate for each individual student.